An Analysis Of The English Textbooks For Elementary School In Kabupaten Sukoharjo Based On The 2003 Local English Curriculum - Hartati, Sri (2005)
The purpose of this research is to know parts of the English textbooks which follow and do not follow the guideline of the 2003 local English curriculum. The writer uses a descriptive qualitative research as the type of research. The data used in this research are taken from document. The data are taken from the English textbooks entitled Enjoy Your English (An English Book for Elementary Students Part one, two, and three) published by Education Department Kabupaten Sukoharjo, Grow with English (An English Course for Elementary School Students Book fourth, fifth and sixth) by Penerbit Erlangga and Go with English (Book fourth, fifth, and sixth) published by Penerbit Yudhistira. The results of the research show that from the data of the 2003 English local curriculum, there are 6 themes with 100 language focuses which should be learnt by the students in the forth class, 7 themes with 32 language focuses for the fifth class and 7 themes with 52 language focuses. Not all of the curriculum suggestions done or written in those 3 textbooks. In "Enjoy Your English" all of the themes and language focuses of the forth, fifth and sixth class are matching with the syllabus suggested and the degree of compatible of it is 100%; in "Grow with English" the appropriate of the themes are 75% for the forth, 33,33% for the fifth years, and 91,67% for the sixth years, and related to the language focuses of it, there is 58% for the forth years, 71,88% for the fifth years, and 65,38% for the sixth years. In the "Go with English", related to the appropriate of the themes, there is 75% for the forth years, 33,33% for the fifth years, and 85,71% for the sixth years; and related to the language focuses, there is 55% for the forth years, 53,13% for the fifth years and for the sixth years 84,62%. Related to the not appropriate parts of the English textbook, in "Enjoy Your English", there is no part of it which is not appropriate with the curriculum. in "Grow with English", the themes which are not appropriate are 25% for the forth, 66,67% for the fifth years, and 8,33% for the sixth years; related to the language focuses, there are 42% for the forth years which are not appropriate, 28% for the fifth years, and 34,62% for the sixth years. In "Go with English", related to the themes which are not appropriate, for the forth years, there is 25%, 66,67% for the fifth years, and 14,29% for the sixth years. Related to the language focuses which are not appropriate, there are 45% for the forth years, 46,88% for the fifth years, and 15,38% for the sixth years.